Controversies in the treatment of incomplete abortion, MVA versus medical treatment with misoprostol - Gutiérrez Ramos, Miguel (2015)
Non-complicated incomplete abortion is one of the most frequent obstetric emergencies in our health facilities, causing high care costs. There are two current modern methods for its attention: manual vacuum aspiration (MVA) and medical treatment with misoprostol, both with the possibility of outpatient management, reducing costs to the health system. Controversies between the two technologies are analyzed and it is concluded that both MVA and misoprostol treatments are modern technologies applicable in gynecology and obstetrics services in our country, with same safety and effectiveness by evidence of many studies conducted.